Fragments of Lead Letters from Nymphaion - Pavlichenko, Natalia; Sokolova, Olga (Hyperboreus, 2017)
In 1984, a few fragments of lead letters were found near the ancient Greek townsite of Nymphaion. These tablets included two fragments without inscriptions, two conjoined fragments with a six line text on one side and a fragment of an opisthograph (six lines on one side, ﬁve on the other). The state of preservation and treatment of the edges of these tablets suggest that we are dealing with fragments of two letters dating from approximately the same period. The palaeographical peculiarities, in particular the upsilon in the form of the Latin letter V on the ﬁrst fragment as well as parallels among Nymphaion grafﬁti on black-glossed vessels as well as a painted one allow us to date all of these fragments to within the broad time span of the late 6th – mid-5th BC, and perhaps, even to a period stretching no later than 475 BC. The fragments are so small that no word written upon them has survived in its entirety and the separation of the words is a complicated task, such that we can only guess of their contents or where their authors and correspondents might be found. However their texts are informative, for instance, they provide yet another example of the use of a personal name that ends with -δωρος in Nymphaion as well as, perhaps, the personal name Μαλία[ς], until now not seen in Nymphaion onomasticon. The term θάλαμ[ος] which relates both to seafaring and architectural lexica is also of interest.